RADIATION THERAPY OF BREAST CANCER WITH ACCOUNT PROGNOSTIC FACTORS - K. A. Simonov; Zh. A. Startseva; E. M. Slonimskaya (Сибирский онкологический журнал, 2016)
This review about the application of radiotherapy in breast cancer patients after radical mastectomy. Emphasizes the need for a differentiated approach to radiation therapy, which should be based on the definition of clinical morphological factors that determine the risk of loco-regional recurrence of breast cancer.